PENGARUH TASK-BASED LANGUAGE TEACHING (TBLT) TERHADAP KEMAMPUAN BAHASA INGGRIS DAN SOFT-SKILLS MAHASISWA S1 KEPERAWATAN UNIMUS - Dodi Mulyadi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2016)
The process of teaching and learning for nursing using TBLT and Soft-skills that suit the learner’s interests and needs contributed to facilitate students’ learning can prepare students for having English communication. The research aimed to find out the effectiveness of implementing the ENP learning model toward students’ English mastery and their Soft-skills improvement. The research employed experimental design using experimental class 40 students and control class 35 students in Semester 2 of year 2015/2016. The data collecting techniques were observation, documentation and questionnaire. The results showed the ENP model of ENP has significant influence on student nurses’ English mastery and their Soft-skills .Keywords: English for nursing purposes (ENP), task-based language teaching (TBLT) and Soft-skills